The effects of observing punishment on consumers’ decisions to punish other companies during industry-wide crises - Chen, Shijiao (Joseph); Li, Yi; Yao, Jun (Journal of the Academy of Marketing Science, 2024)
Industry-wide crises, characterized by multiple companies within an industry allegedly engaging in similar misconduct, lead to disruptions in the social order. During such crises, one or a few of the involved companies often attract more media attention and receive punishment ahead of the others. Will such punishments take the heat off other involved companies or increase their risk of further punishment? This research shows that the observation of these punishments increases consumers’ intent to punish other involved companies. Observing one involved company get punished signals that the involved companies are indeed at fault, thereby increasing consumers’ certainty in blame attribution. Subsequently, consumers increase their motive to restore social order and their intent to punish other involved companies. Four theoretically and managerially relevant moderators have been identified and tested. Seven studies involving secondary data and experiments with both hypothetical and real behavioral outcomes support the proposed effects.